Lipoarabinomannan in Active and Passive Protection Against Tuberculosis - Correia-Neves, Margarida (Front Immunol, 2019)
Glycolipids of the cell wall of Mycobacterium tuberculosis (Mtb) are important immunomodulators in tuberculosis. In particular, lipoarabinomannan (LAM) has a profound effect on the innate immune response. LAM and its structural variants can be recognized by and activate human CD1b-restricted T cells, and emerging evidence indicates that B cells and antibodies against LAM can modulate the immune response to Mtb. Anti-LAM antibodies are induced during Mtb infection and after bacille Calmette–Guerin (BCG) vaccination, and monoclonal antibodies against LAM have been shown to confer protection by passive administration in mice and guinea pigs. In this review, we describe the immune response against LAM and the potential use of the mannose-capped arabinan moiety of LAM in the construction of vaccine candidates against tuberculosis.